Howell-Jolly bodies and liver-spleen scanning for assessment of splenic filtrative function yields discordant results in renal transplant recipients. Issue 51 (December 2017) - Araújo, Nordeval Cavalcante; Orlando, Margarida Maria Camões; Neves, Moises Bonifácio; Rioja, Suzimar Silveira; de Lucena, Stella Beatriz Gonçalves; Mandarim-de-Lacerda, Carlos Alberto
Abstract : Abstract: Given discrepancies between methods for diagnosing hyposplenism, the purpose of this study was to evaluate the effect of the spleen size on the correlation between the methods, and to propose a model for improving the interpretation. Patients with renal allografts were included, in whom the spleen was assessed using Doppler ultrasound, scintiscan, and the presence of Howell-Jolly bodies (HJBs) in peripheral smears. In 35 subjects, scintiscan and HJBs were normal (Group 0); 20 had an abnormal result in both methods (Group 1); 34 had discordant results with HJBs present (Group 2); and 14 had discordant results with decreased spleen uptake (Group 3). There was no association between HJBs and scintiscan. The patients of Groups 1 and 2 had smaller spleens. The patients with smaller spleen had more hematological evidence of hyposplenism and exhibit smaller discrepancies between the methods than patients with larger spleen. The spleen can tip the balance from a normal to impaired function provided that the spleen size is below the critical mass required to maintain splenic function. A mild impairment of phagocytic function and slight dyserythropoiesis along with a small spleen would result in decreased take up of radiocolloid or the appearance of HJBs in blood smears.